Fungal extracts as biocontrol of growth, biofilm formation, and motility of xanthomonas citri subsp. citri - Luján, Enrique Ernesto (2019)
For the present work, Metarhizium rileyi, a common entomopathogenic fungus, was grown in batch conditions in the absence and presence of its host, Spodoptera frugiperda, to obtain secondary metabolites with potential antimicrobial effect. The extraction of secondary metabolites was carried out by using two solvent systems for the biomass (ethyl acetate and methanol), while secondary metabolites present in the supernatant were extracted by using ethyl acetate as extraction solvent. These extracts were evaluated for their inhibitory effect on the growth, biofilm formation, and motility of three Xanthomonas citri subsp. citri strains (Xcc20, Xcc29, and Xcc42). The in vivo effect of these extracts to prevent the development of cankers on grapefruit leaves was also evaluated.M. rileyi biomass ethyl acetate extracts in the presence and absence of its host had a strong inhibitory effect on Xcc strains growth. On the other hand, the presence of S. frugiperda as an elicitor significantly increased M. rileyi?s inhibitory capacity to form a biofilm. A different behavior was observed for the copper resistant strain, Xcc42, for its biofilm formation and swimming capacity since the most active samples were the supernatant extracts in the presence andabsence of S. frugiperda. Our results suggest that the most important factor for in vivo canker development is the inhibition of Xcc?s motility since all the extracts that inhibited canker development in vivo were also able to inhibit Xcc20?s motility in vitro. The fact that the extracts can prevent cankers development in vivo indicates they are promising sources of metabolites to prevent the development of this citrus disease.